Tied down: Tethering redox proteins to the outer membrane in Neisseria and other genera - Xi Li (2018)
Typically, the redox proteins of respiratory chains in Gram-negative bacteria are localized in the cytoplasmic membrane or in the periplasm. An alternative arrangement appears to be widespread within the betaproteobacterial genus Neisseria, wherein several redox proteins are covalently associated with the outer membrane. In the present paper, we discuss the structural properties of these outer membrane redox proteins and the functional consequences of this attachment. Several tethered outer membrane redox proteins of Neisseria contain a weakly conserved repeated structure between the covalent tether and the redox protein globular domain that should enable the redox cofactor-containing domain to extend from the outer membrane, across the periplasm and towards the inner membrane. It is argued that the constraints imposed on the movement and orientation of the globular domains by these tethers favours the formation of electron-transfer complexes for entropic reasons. The attachment to the outer membrane may also affect the exposure of the host to redox proteins with a moonlighting function in the host-microbe interaction, thus affecting the host response to Neisseria infection. We identify putative outer membrane redox proteins from a number of other bacterial genera outside Neisseria, and suggest that this organizational arrangement may be more common than previously recognized. ©The Authors Journal compilation ©2011 Biochemical Society.